Pedro Pons' sign as a Brucellosis complication - Nazan Tuna; Aziz Ogutlu; Hasan Tahsin Gozdas; Oguz Karabay (Wolters Kluwer Medknow Publications, 2011)
Brucellosis is one of the most important zoonotic diseases. Several complications may be seen during its clinical course. Here, we describe a patient who presented with complaints of fatigue, malaise, and intensive lumbar pain. He had been suffering from these complaints for nearly 1 month. It was learned that he lived in rural area, made and ate his own cheese. The Rose Bengal test was positive and Brucella standard tube agglutination was positive at 1/320 titer. Pedro Pons' sign, an osteoarticular complication of brucellosis, was revealed with the aid of radiologic imaging. Osteoarticular involvement is common in the course of brucellosis. Deformation in vertebrae formerly known as Pedro Pons' sign should be thought in brucellosis patients suffering from lumbar pain.